Technical Features and User Reviews in the Smartphone Industry: The Four Market Leaders at a Glance - Francesca MICHELINO; Vincenzo VARRIALE; Antonello CAMMARANO; Mauro CAPUTO (Communications of International Proceedings, 2020)
The paper analyzes the relationships between smartphone performances as to various technical features and scores obtained in user reviews for Samsung, Apple, Huawei and Xiaomi. Results show that usability is the feature that mostly influence the value for customers; significant value is also attributed to screen, dimension and manufacturing quality.
Keywords: User review; smartphone; Apple; Huawei; Samsung; Xiaomi.